PENGARUH LOKASI USAHA DAN KOMPETENSI KEWIRAUSAHAAN TERHADAP KEBERHASILAN USAHA - Muhammad Iffan; Srifana Suharlin (Journal of Economics, Management, Business and Accounting (JEMBA), 2022)
The motivation behind the exploration led is to find out the impact of the business area and innovative skills on business achievement at the Coffee Shop in Sumur Bandung District, both partially and simultaneously. There is a population of 39 business actors and obtained 39 respondents using saturated example methods where everyone from the population is examined. The research in this study uses graphs and is certain. Through this strategy will find out the great relationship between factors and produce conclusions from the object being researched. This exploration shows the impact between Business Location and Entrepreneurship Competence on Business Success at Coffee Shops in Bandung Well District, this is shown by T calculating more important than T table and can be resolved there is a positive impact between Area and Business Capability on Business Results at Coffee Shop in Bandung Well District.